2018
DOI: 10.2147/ndt.s150550
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to riluzole in patients with amyotrophic lateral sclerosis: an observational study

Abstract: ObjectiveRiluzole is the first drug approved to treat amyotrophic lateral sclerosis (ALS). Recently, an oral suspension (OS) of riluzole was made available. Thus, the aim of our study was to evaluate the adherence to 2 formulations of riluzole in patients with ALS.Patients and methodsWe enrolled 45 consecutive patients with ALS. At disease diagnosis, riluzole was prescribed in 2 different formulations depending on the severity of dysphagia (27/45 patients received tablets and 18/45 patients received OS). Side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…In general, studies of treatment adherence in ALS have not typically characterized non-motor symptoms in patient cohorts [e.g., physiotherapy exercises ( 42 ); respiratory support ( 43 ); tolerability of oral vs. tablet Riluzole ( 44 ); tolerability of early non-invasive ventilation use ( 45 )] and is an exclusionary criteria in some studies [e.g., aerobic exercise therapy vs. cognitive behavioral therapy ( 46 )]. It is therefore not surprising that motor predictors of treatment adherence are often reported.…”
Section: The Impact Of Cognitive and Behavioral Symptoms On Treatmentmentioning
confidence: 99%
“…In general, studies of treatment adherence in ALS have not typically characterized non-motor symptoms in patient cohorts [e.g., physiotherapy exercises ( 42 ); respiratory support ( 43 ); tolerability of oral vs. tablet Riluzole ( 44 ); tolerability of early non-invasive ventilation use ( 45 )] and is an exclusionary criteria in some studies [e.g., aerobic exercise therapy vs. cognitive behavioral therapy ( 46 )]. It is therefore not surprising that motor predictors of treatment adherence are often reported.…”
Section: The Impact Of Cognitive and Behavioral Symptoms On Treatmentmentioning
confidence: 99%
“…In this study, ALS patients who showed ALT and AST levels > 3× of the upper limit of the normal level [2, 12] and presented with accompanying subjective symptoms, such as anorexia, nausea, and dizziness, were considered cases/patients with abnormal elevated liver enzymes. In discontinuation cases, biochemical analyses revealed abnormally elevated liver enzymes in five cases and elevated Krebs von den Lungen-6 (KL-6) and surfactant protein (SP)-D levels in four pneumonia cases.…”
Section: Resultsmentioning
confidence: 99%
“…Data regarding sex, age, disease type, initial symptoms, biochemical analyses before and after riluzole administration, and medical events and histories were recorded. When alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels were > 3× the upper limit of the normal level [2, 12] and accompanied by additional subjective symptoms, such as anorexia, nausea, or dizziness, liver dysfunction was considered and riluzole was discontinued. In addition, in cases of withdrawal, causes of discontinuation and durations of disease and drug administration were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The current TNFα inhibitor thalidomide shows some promising results in animal models of FUS-ALS but does not appear to be effective in regulating disease progression in patients (Kia et al 2018). Riluzole blocks glutamate-mediated excitatory neurotransmission to reduce excitotoxicity and is currently the only drug of life to prolong ALS patients (Introna et al 2018). Bulbus medullae group 3.56/4.00 5.60/5.00 3.80/3.10 8.00/5.00 Cervical spinal cord group 3.79/4.00 2.60/5.00 3.20/3.10 5.50/5.00 Lumbosacral spinal cord group 3.80/4.00 6.70/5.00 3.20/3.10 8.30/5.00 (Koroglu et al 2017).…”
Section: Fus (Fused In Sarcoma Protein)mentioning
confidence: 99%